O DISPOSITIVO METODOLÓGICO E INTERVENTIVO AUTOCONFRONTAÇÃO E SEUS USOS EM PESQUISAS DE EDUCAÇÃO - Perez, Deivis; Messias, Carla (Nuances: estudos sobre Educação, 2014)
This article presents an academic and scientific study about the use of the device methodological and intervening of selfconfrontation in research in post-graduate studies in Education in Brazil. The self-confrontation is a device created by linguist Daniel Faïta and perfected by psychologist Yves Clot. She seeks to capture the multiple discourses and perspectives around a particular craft, integrating researcher and workers to facilitate the installation of a dialectical movement of analysis and production of knowledge about the work, ownership of these knowledge workers and the collective transformation of labor activity. We chose a qualitative approach and the realization of documental analysis of the abstracts of researches that resulted in the production of doctoral theses and dissertations held in Brazil between 1987 and 2011. Were examined studies that had their abstracts gathered and made available by the Coordenadoria de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) on its website. The results show that self-confrontation is used piecemeal studies produced in the area of Education, used primarily to collect data and to give less emphasis to the transformation of the labor process. http://dx.doi.org/10.14572/nuances.v24i3.2699